PENYELEWENGAN TUJUAN PENDIRIAN BADAN USAHA PENUNJANG KEGIATAN OLEH LEMBAGA YAYASAN DALAM PERSPEKTIF UNDANG-UNDANG YAYASAN - Ida Bagus Bayu Brahmantya (Kerta Dyatmika, 2020)
This research is entitled "Misappropriation of Establishment Objectives of Supporting Business Activities by Foundation Institutions in Foundation Law Perspectives." The background of this research is the opportunity to misuse Foundation institutions that can occur because the Foundation can carry out business activities to achieve the aims and objectives of establishing the Foundation with how to set up a business entity or participate in a business entity. Article 5 of the Foundation Law stipulates that the wealth of the Foundation, including the proceeds of the Foundation's business activities, is the full wealth of the Foundation to be used to achieve the aims and objectives of the Foundation. Criminal provisions against violations of the Article are regulated in Article 70 of the Foundation Law, for those who violate the provisions of imprisonment for a maximum of 5 (five) years and are obliged to return it. Article 6 of the Foundation Law is used as a shield against the prohibition. This study focuses on two legal issues, namely, how is the Foundation's business activities to obtain profits as capital in managing the Foundation according to the Foundation Law? And what about sanctions for misappropriation of a Foundation's business activities according to the Foundation Law? The research method used in analyzing legal issues in this study is the normative legal research method. This normative legal research is carried out using the statutory approach, the historical approach to the comparative approach. Based on the analysis, it is known that the Foundation Law uses the method of prevention by including provisions that do not allow or at least, complicating the misuse of the foundation by the organs of the Foundation. However, in the Foundation Law there is a legal obscurity that affects the attitude and quantity of non-compliance and has a real effect on legal behavior, including the behavior of lawbreakers. Keywords: Foundation, Criminal, Business Entity, Misappropriation.